2014
DOI: 10.1128/jvi.01415-14
|View full text |Cite
|
Sign up to set email alerts
|

The Tegument Protein pp65 of Human Cytomegalovirus Acts as an Optional Scaffold Protein That Optimizes Protein Uploading into Viral Particles

Abstract: The mechanisms that lead to the tegumentation of herpesviral particles are only poorly defined. The phosphoprotein 65 (pp65) is the most abundant constituent of the virion tegument of human cytomegalovirus (HCMV). It is, however, nonessential for virion formation. This seeming discrepancy has not met with a satisfactory explanation regarding the role of pp65 in HCMV particle morphogenesis. Here, we addressed the question of how the overall tegument composition of the HCMV virion depended on pp65 and how the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 67 publications
(95 reference statements)
5
39
1
Order By: Relevance
“…11,67,71,72 Immunofluorescence analysis in normal HCMV infected fibroblasts showed that pp65 was not present in all viral ACs (data not shown), a fact which is in agreement with previous studies reporting that pp65 serves as an optional scaffold protein for virion formation. 73 The same was also true for pUL97 (data not shown). Moreover, in RhoB-knockdown HCMV infected cells, residual RhoB could be detected at the AC by immunofluorescence (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…11,67,71,72 Immunofluorescence analysis in normal HCMV infected fibroblasts showed that pp65 was not present in all viral ACs (data not shown), a fact which is in agreement with previous studies reporting that pp65 serves as an optional scaffold protein for virion formation. 73 The same was also true for pUL97 (data not shown). Moreover, in RhoB-knockdown HCMV infected cells, residual RhoB could be detected at the AC by immunofluorescence (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…8C), which is reminiscent of the phenotype observed in HSV-1 VP22-null mutants (70,74). We speculate that KSHV ORF52 reinforces the interaction network between virion proteins, much as HSV-1 VP22 and HCMV pp65 do (62,72). The shared and unique structural features and functions of ORF52 homologues in KSHV, MHV-68, RRV, and EBV allude to the common, yet distinct strategies employed by these viruses to maintain persistent infection of their human host.…”
Section: Discussionmentioning
confidence: 74%
“…Similar interactions between tegument proteins of betaherpesviruses have also been reported. The most abundant tegument protein of HCMV, pp65 (pUL83), interacts with pUL25 and pUL43 (60,61), and the loss of pp65 impairs the incorporation of other tegument proteins into virions (62). Interactions among gammaherpesvirus-specific tegument proteins may also exist (38,48,52,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…3A–3C). All cell types expressed both the major immediate early and the pp65 late protein by immunofluorescent staining [25]. Pericytes also expressed the pp28 late antigen (insert Fig.…”
Section: Resultsmentioning
confidence: 99%